HUBUNGAN KEIKUTSERTAAN KELAS IBU HAMIL DENGAN PENGETAHUAN KEHAMILAN PERSALINAN DAN NIFAS - Asa Ulia Kusuma; Laksmi Maharani (Fakultas Kedokteran Universitas Trisakti, 2026)
Pregnant women classes were educational programs aimed at improving maternal knowledge and preparedness in facing pregnancy, childbirth, and the postpartum period. Adequate knowledge was important for pregnant women to understand physiological changes during pregnancy, adopt positive health behaviors, and recognize danger signs of pregnancy, thereby contributing to the prevention of pregnancy complications and reduction of maternal mortality. This study aimed to analyze the relationship between participation in pregnant women classes and the level of maternal knowledge. This study used an analytical design with a cross sectional approach involving third trimester pregnant women in the working area of Grogol Petamburan Primary Health Center, West Jakarta. A total of 113 respondents were selected using consecutive sampling. Data were collected using structured questionnaires and analyzed using the chi square test. The results showed a significant relationship between participation in pregnant women classes and maternal knowledge level with a p value of 0.001. Pregnant women who participated in the classes tended to have better knowledge compared to those who did not participate. It can be concluded that participation in pregnant women classes was significantly associated with improved maternal knowledge, therefore active involvement of health workers is recommended to enhance socialization and encourage regular participation of pregnant women in these classes.